A Study of Neuron Growth on Micropatterned PDMS Surfaces - Ellner, Avram A. (Tufts Archival Research Center, 2016)
A study of embryonic rat neuron growth on micropatterned PDMS surfaces whose topography channeled axon growth along the surfaces' ridges.